Back on track - digital health applications to treat back pain of rheumatic patients?: Results of a qualitative interview study : observational research - Boy, Katharina; May, Susann; Labinsky, Hannah; Morf, Harriet; Heinze, Martin; Leipe, Jan; Kuhn, Sebastian; Schett, Georg; Knitza, Johannes; Mühlensiepen, Felix (Rheumatology international, 2024)
Non-specific low back pain (NLBP) is prevalent among patients with rheumatic conditions. Digital health applications (DiGAs) provide reimbursed, personalized home treatment for patients, promising to overcome limitations of traditional healthcare systems. However, the adoption and effectiveness of back pain-specific DiGAs in rheumatology are not well understood. This study aims to explore the experiences and perspectives of a diverse group of rheumatology stakeholders regarding the use of DiGAs for back pain management. Qualitative interviews and a focus group discussion were conducted with a wide range of stakeholders including rheumatic patients, rheumatologists, nurses and DiGA producers. The data were analysed using qualitative content analysis. The study included 15 interviews (10 rheumatic patients, 4 rheumatologists, 1 DiGA producer) and 1 focus group with mixed participants (n = 12). Most stakeholders valued the instant access to personalized and effective back pain treatment provided by DiGAs. Patients appreciated the flexibility and ease of use of DiGAs which can be used anywhere and anytime. Concerns were raised about insufficient guidance regarding correct execution of exercises, which was seen as potentially dangerous and unsettling for patients. Healthcare professionals (HCPs) highlighted barriers, such as the lack of reimbursement, time constraints, and inadequate DiGA-specific education as barriers to prescribing DiGAs. Additionally, poor patient onboarding often led to delays, increased skepticism, and premature discontinuation of therapy. Stakeholders emphasized the challenges of current care driven by a shortage of HCPs and generally supported usage of back pain DiGAs. Various barriers and solution approaches were identified to enhance the performance, usability, and implementation of DiGAs in rheumatology.